2013
DOI: 10.1002/ange.201208550
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Domain Swaps Provide Insights into the Rules of Fungal Polyketide Synthase Programming and the Rational Synthesis of Non‐Native Aromatic Products

Abstract: Nach den Regeln spielen: Der kombinatorische Domänenaustausch zwischen „abgebauten“ nichtreduzierenden Polyketid‐Synthasen (NR‐PKSs) deckt die Regeln auf, nach denen der Zusammenbau der Produkte erfolgt. Die von einzelnen katalytischen Domänen ausgeübte Kontrolle ist genügend groß, damit Heterokombinationen von Domänen unterschiedlicher NR‐PKSs Produkte in vorhersagbarer Weise synthetisieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Collectively, these experiments show that the F-or S-type regiospecificities of first-ring cyclizations are solely programmed into the PT domains of collaborating nrPKSs (29,35). This programming is portable among nrPKS platforms, without influencing starter unit choice or the number of extensions carried out by the rest of the chassis.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Collectively, these experiments show that the F-or S-type regiospecificities of first-ring cyclizations are solely programmed into the PT domains of collaborating nrPKSs (29,35). This programming is portable among nrPKS platforms, without influencing starter unit choice or the number of extensions carried out by the rest of the chassis.…”
Section: Resultsmentioning
confidence: 87%
“…Recent experiments to replace PT domains in nrPKS model systems showed that the register of F-type aldol condensations may be switched (29,35), with the incoming PTs enforcing a subtle shift of the substrate chains in the catalytic chambers to expose different carbons (C2, C4, or C6) to the catalytic histidine for deprotonation and enolate formation (10). Thus, we were interested to see whether first-ring cyclizations may also be reconfigured between F-and S-type folding modes by exchanging PT domains.…”
Section: Resultsmentioning
confidence: 99%
“…The last step of BDL scaffold biosynthesis is the release of the product, catalyzed by an O-C bond-forming thioesterase (TE) domain of the nrPKS. TE domains form the BDL macrolactone using the ω-1 alcohol as a nucleophile, but may use alternative nucleophiles such as the C9 enol to yield α-pyrones or water or alcohols from the media to form acyl resorcylic acids (ARAs), acyl dihydroxyphenylacetic acids (ADAs), and their esters (18)(19)(20)(21)(22). iPKSs that produce BDLs in the RAL 14 , RAL 12 , and DAL 12 subclasses have been characterized and reconstituted both in vivo by heterologous expression in yeast and in vitro using isolated recombinant iPKS enzymes (11)(12)(13)(14)(23)(24)(25).…”
Section: Significancementioning
confidence: 99%
“…iPKSs that produce BDLs in the RAL 14 , RAL 12 , and DAL 12 subclasses have been characterized and reconstituted both in vivo by heterologous expression in yeast and in vitro using isolated recombinant iPKS enzymes (11)(12)(13)(14)(23)(24)(25). Domain exchanges among different BDLSs were used to decipher some of the programming rules of these enzymes and yielded a limited number of structurally diverse unnatural products (3,18,20,21,26,27).…”
Section: Significancementioning
confidence: 99%
“…A biossíntese de compostos oriundos das rotas híbridas PKS-NRPS de fungos filamentosos ainda não é conhecida com detalhamento suficiente para que os domínios funcionais dessas enzimas possam ser manipulados com precisão (FISCH, 2013). A manipulação e dissecação de domínios em fungos filamentosos é uma prática bastante recente e tem sido realizada somente em enzimas PKS não-redutoras (NR-PKS) YEH et al, 2013;XU et al, 2013;VAGSTAD et al, 2013;AHUJA et al, 2012;ITOH et al, 2012;LIU et al, 2011 Alguns dos pontos discutidos acima, que eventualmente podem estar envolvidos na falta de sucesso desse experimento de engenharia químico-genética, apenas mostram como o processo como um todo é altamente complexo e a sua realização está sujeita à interferência de diversos fatores.…”
Section: Construções No Vetor Deg2unclassified